(untitled) (Research, Society and Development, 2023)
This article presents a study on the sustainability-inducing instrument in family farming, which aims to promote and reconcile economic development and environmental preservation in family farming. The objective is to discuss these themes from the critical perspective of various authors for whom development works as an emancipatory element for people, seeks to reduce risks, and implements a dialogue-inducing instrument for public policies that incentivize the protection and conservation of the environment, which are linked to the realities and demands of family farming. The analysis focuses on government strategies, including the implementation of family farming as a protector of environmental services and the limits and possibilities of the Law of Payment for Environmental Services. It is concluded that there is an important effort by executive bodies to implement the PSA (Payment for Environmental Services) in family farming, which contributes to productive diversification, job and income generation, and food security. However, family farming faces challenges regarding sustainability, such as a lack of access to technology and markets, soil degradation, and loss of biodiversity. Thus, payment for environmental services will play a fundamental role in promoting family farming and sustainable development.